The Effect of Mindfulness-Based Intervention on Brain-Derived Neurotrophic Factor (BDNF): A Systematic Review and Meta-Analysis of Controlled Trials - Gomutbutra, Patama; Yingchankul, Nalinee; Chattipakorn, Nipon; Chattipakorn, Siriporn; Srisurapanont, Manit (Frontiers in Psychology, 2020)
Background: This systematic review aimed to answer three questions. First, how much do Mindfulness-Based Interventions (MBI) affect peripheral Brain-Derived Neurotrophic Factor (BDNF)? Second, do mindfulness exercise-based interventions (exercise-MBI) and mindfulness meditation-based interventions (meditation-MBI) affect peripheral BDNF differently? Third, does the age of MBI and the accumulative hours of MBI practice affect peripheral BDNF? Methods: We included randomized controlled trials in adults (age >18-year-old) comparing MBI and no intervention that reported the peripheral BDNF. Database searches included PubMed, CINAHL, CENTRAL, PsyInfo, and Scopus. Two reviewers independently selected the studies and assessed the trial quality. We used the standardized mean difference (SMD) as the effect size index and conducted moderator analyses. Results: Eleven studies were included in this systematic review. Five and three studies applying exercise-MBI and meditation-MBI were included in the meta-analysis (N=479). The pooled effect size showed a significantly greater increase of peripheral BDNF in MBI groups compared to the control groups (k=8, N=479, SMD = 0.72, 95%CI 0.31 to 1.14, I2=78%). Significant more increases of BDNF in the MBI groups were found in both subgroups of Exercise-MBI and Meditation-MBI. The effect sizes of both subgroups were not significantly different between subgroups (2=0.02, p=0.88). We found no significant correlation between the effect sizes and participants’ age (r=-0.0095, p =0.45) or accumulative hours of practice (r=0.0021, p =0.57). Conclusion: The heterogeneous data of this small sample-size meta-analysis suggests that Mindfulness-Based Interventions can increase peripheral Brain-Derived Neurotrophic Factor. Either Mindfulness Exercise or Mindfulness meditation-based Interventions can increase peripheral Brain-Derived Neurotrophic Factor.